Attitudes toward, knowledge of, and beliefs regarding providing care to LGBT patients among student nurses, nurses, and nursing educators: A cross-sectional survey. (September 2022) - Wang, Ya-Ching; Miao, Nae-Fang; You, Mei-Hui
Abstract: Background: Studies have assessed attitudes toward, knowledge of, and beliefs regarding providing care for lesbian, gay, bisexual, and transgender (LGBT) patients among student nurses, nurses, and nursing educators individually, but few studies have compared these aspects among these groups. Objectives: To examine the attitudes toward, knowledge of, and beliefs regarding providing care for LGBT patients among student nurses, nurses, and nursing educators in Taiwan. Design: Cross-sectional survey. Settings: The study was advertised in 8 nursing schools, 14 nursing associations, 209 nursing homes, and 2 online chatrooms in Taiwan. Participants: A total of 1150 participants were recruited: 447 student nurses, 475 nurses, and 228 nursing educators. Methods: Data were collected between August 2021 and January 2022 through a questionnaire with five sections: demographics, knowledge of LGBT health, the Knowledge about Homosexuality Questionnaire, the Attitude Toward Lesbian and Gay Men Scale, and the Gay Affirmative Practice Scale. Results: The results suggest that the participants had limited knowledge of LGBT health. The nursing educators had the lowest scores for knowledge of LGBT health and homosexuality and the most negative attitudes toward lesbians and gay men among the groups; however, they were most likely to report their beliefs regarding providing nursing care to LGBT patients than the other two groups. Conclusions: The results indicate the importance of providing nursing educators with training courses and resources related to culturally competent care to improve education for nursing students and care for LGBT patients. Highlights: Student nurses, nurses, and nursing educators in Taiwan exhibited limited knowledge of LGBT health. Nursing educators had the lowest scores for knowledge of LGBT health and homosexuality. Nursing educators were more likely to have negative attitudes towards lesbians and gay men. Nursing educators were more likely to report awareness of gay affirmative practice than student nurses and nurses.